2021
DOI: 10.3390/polym13091434
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of DBD Plasma Activation Time on the Dyeability of Woven Polyester Fabric with Disperse Dye

Abstract: This study consists of two parts. In the first, the woven polyester fabric, after washing to remove lubricant oils, was treated with the dielectric barrier discharge (DBD) plasma at the short plasma exposure time (from 15 to 90 s). The effect of the plasma exposure time on the activation of the polyester fabric was assessed by the wicking height of the samples. The results show that the wicking height in the warp direction of the plasma-treated samples improved but was virtually unchanged in the weft direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This phenomenon has also been observed for polyester fabric after low pressure plasma treatment using a mixture of nitrogen, oxygen and argon [ 26 ] and after DBD treatment [ 23 , 25 ]. These phenomena have been explained by the appearance of new polar functional groups containing oxygen under the influence of the plasma environment, as confirmed by XPS analysis of the plasma treated PET samples [ 23 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…This phenomenon has also been observed for polyester fabric after low pressure plasma treatment using a mixture of nitrogen, oxygen and argon [ 26 ] and after DBD treatment [ 23 , 25 ]. These phenomena have been explained by the appearance of new polar functional groups containing oxygen under the influence of the plasma environment, as confirmed by XPS analysis of the plasma treated PET samples [ 23 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 52%
“…This phenomenon has also been observed for polyester fabric after low pressure plasma treatment using a mixture of nitrogen, oxygen and argon [ 26 ] and after DBD treatment [ 23 , 25 ]. These phenomena have been explained by the appearance of new polar functional groups containing oxygen under the influence of the plasma environment, as confirmed by XPS analysis of the plasma treated PET samples [ 23 , 25 , 26 , 27 ]. Work [ 23 ] also suggested that the surface roughness and especially the appearance of grooves on the fiber surface due to plasma action could partly explain the increase in the wicking height of the PET fabric.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations